Theism and Realism: God in the (Humanly Constituted) World (2022)
ABSTRACT: This paper attempts to delineate a kind of realism, which incorporates some anti-realistic insights regarding the perspective, situated, and historical character of our forms of knowing and being in the world, and which resonates with the basic tenets of Christian theism. The first part of the paper analyzes the challenges anti-realism poses to Christian theism, particularly regarding the role, which the doctrine of creation played in securing the correspondence theory of truth as well as the fundamental experience of God as the foundation of order and meaning. Using Heidegger’s hermeneutics in the second part, it is shown that epistemic pluralism can be made compatible with realism. Given that this form of hermeneutic realism still has problems with integrating the transcendence of God, as well as his/her presence and action in the “world,” the notion of continuous co-creation as the basis for a pluralist realism that is amenable to Christian theism is explored in the final part.